Wavelength-Tunable Ultra-Stable Optical Frequency Comb Based on All-Polarization-Maintaining Fiber Laser - He, Xin; Zhang, Pan; Zhang, Yanyan; Lin, Qimeng; Guo, Hongyu; Hou, Lei; Wang, Kaige (Frontiers in Physics, 2020)
This study details the implementation of a wavelength-tunable ultra-stable optical frequency comb (OFC), which is generated by a passively mode-locked all-polarization-maintaining Erbium (Er)-doped fiber laser based on a nonlinear amplifying loop mirror. The center wavelength can be tuned from 950 nm to 1080 nm and from 1650 nm to 2080 nm by adjusting the pump’s power. Standard deviations of 100 μHz (τ=1 s) for repetition rate and 330 μHz (τ=1 s) for carrier-envelop offset frequency were measured in 15 hours. The corresponding Allan deviations were 2.4×10-17 and 8.2×10-17 at 1 s. The repetition rate and carrier-envelop offset frequency of OFC were counted by a П-type counter from K+K Messtechnik.